Quality Improvement of Education Based on School-Based Management at Madrasah Aliyah Negeri 1 Deli Serdang - Leli Hasanah Lubis; Dwina Putri; Ali Sadikin Ritonga; Azhar Azhar; Haris Suwondo (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the implementation of SBM at Madrasah Aliyah Negeri 1 Plus Skills Deli Serdang which includes education staff management, student management, curriculum management, facility and infrastructure management, financial management, and community relations management. This research uses a type of qualitative research using descriptive research. Data were obtained from the Deli Serdang 1 Plus Skills Madrasah Aliyah Negeri. While the data collection technique in research is the interview method. Secondary data or data reinforcement obtained by the observation method, and documentation whose data sources are from the Head of Madrasah and staff at Madrasah Aliyah Negeri 1 Plus Skills Deli Serdang. Data analysis begins by collecting all data from various sources, checking the validity of the data, presenting data and verifying data using triangulation techniques. The results of the study show that the results of the implementation of school-based management at Madrasah Aliyah Negeri 1 Plus Skills Deli Serdang have been going quite well, although in practice there are still many obstacles and obstacles in each component of the field of school management, but this has become a motivation for madrasas to bring out madrasa creativity. in developing programs that are more in line with the needs and potential of madrasas to improve the quality of education in madrasah.